New guys around the block - Guy, Rosa. (London : Puffin, 1983)
Harlem teenager Imamu Jones, repainting his mother's apartment, hoping to help her overcome her alcholism, is troubled as he begins to suspect one of his friends may be quality of a series of burglaries and other crimes.
Keywords: Afro-Americans -- Fiction; Mystery and detective stories; Harlem (New York N.Y.) -- Fiction